Transcriptomic response of yeast cells to ATX1 deletion under different copper levels. (December 2016) - Cankorur-Cetinkaya, Ayca; Eraslan, Serpil; Kirdar, Betul
Abstract Background Iron and copper homeostatic pathways are tightly linked since copper is required as a cofactor for high affinity iron transport. Atx1p plays an important role in the intracellular copper transport as a copper chaperone transferring copper from the transporters to Ccc2p for its subsequent insertion into Fet3p, which is required for high affinity iron transport. Results In this study, genome-wide transcriptional landscape ofATX1 deletants grown in media either lacking copper or having excess copper was investigated.ATX1 deletants were allowed to recover full respiratory capacity in the presence of excess copper in growth environment. The present study revealed that iron ion homeostasis was not significantly affected by the absence ofATX1 either at the transcriptional or metabolic levels, suggesting other possible roles for Atx1p in addition to its function as a chaperone in copper-dependent iron absorption. The analysis of the transcriptomic response ofatx1∆/atx1∆ and its integration with the genetic interaction network highlighted for the first time, the possible role ofATX1 in cell cycle regulation, likewise its mammalian counterpartATOX1, which was reported to play an important role in the copper-stimulated proliferation of non-small lung cancer cells. Conclusions The present finding revealed the dispensability of Atx1p for the transfer of copper ions to Ccc2p and highlighted its possible role in the cell cycle regulation. The results also showed the potential ofSaccharomyces cerevisiae as a model organism in studying the capacity ofATOX1 as a therapeutic target for lung cancer therapy.